Health and well-being in eye care practice: Negotiating with your patient's ocular health and well-being. Issue 7 (July 2021) - Retallic, Neil; Shah, Sheena
Abstract : Health care is under greater pressure than ever before, Neil Retallic and Sheena Shah ask the question… as eye care professionals how can we gain concurrence from our patients to follow our professional advice regarding their ocular and mental health?.